2019
DOI: 10.1007/s11116-019-10010-0
|View full text |Cite
|
Sign up to set email alerts
|

Steering short-term demand for car-sharing: a mode choice and policy impact analysis by trip distance

Abstract: Car-sharing could have substantial benefits. However, there is not enough evidence about if more people choosing car-sharing would reduce private car usage or public transport demand. This work aims to bring forward some insights by studying short-term car-sharing choice behavior. A mode choice analysis is conducted first followed by a simulation analysis to evaluate modal substitution pattern. Policy implications are obtained in terms of the possible measures that could effectively bring down private car usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Thus, the VOT of carsharing is 35.56 RMB Yuan (5.08 US Dollar)/h calculated by the ratio between the coefficients of car in-vehicle time and carsharing fare, which is less than the sample average hourly wage of 61 RMB Yuan (8.71 US Dollar)/h (the average monthly income of the sample is 10.6 K RMB Yuan, and the normal working hours per year is 2080 h) and is within a reasonable range. The result in this paper is consistent with that in Li's research [47], but smaller than that in De Luca [25]. In the former research in Taiyuan, China, the VOT is 22.0 RMB Yuan (3.14 US Dollar)/h in mid-distance (2-5 km) trip and 81.1 RMB Yuan (11.59 US Dollar)/h in long-distance (more than 5 km) trip.…”
Section: Model Estimation Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the VOT of carsharing is 35.56 RMB Yuan (5.08 US Dollar)/h calculated by the ratio between the coefficients of car in-vehicle time and carsharing fare, which is less than the sample average hourly wage of 61 RMB Yuan (8.71 US Dollar)/h (the average monthly income of the sample is 10.6 K RMB Yuan, and the normal working hours per year is 2080 h) and is within a reasonable range. The result in this paper is consistent with that in Li's research [47], but smaller than that in De Luca [25]. In the former research in Taiyuan, China, the VOT is 22.0 RMB Yuan (3.14 US Dollar)/h in mid-distance (2-5 km) trip and 81.1 RMB Yuan (11.59 US Dollar)/h in long-distance (more than 5 km) trip.…”
Section: Model Estimation Resultssupporting
confidence: 88%
“…The roughly equal cross elasticities of carsharing fare on motor mode and public transit mode indicates that the increasing demand mainly comes from both motor and public transit modes. Therefore, the policy measures on private car are in absolute need and should be implemented alongside any carsharing promotion policies [47]. (3) When the number of companions increases, commuters are more willing to use carsharing.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, in a study examining the effects of free-floating carsharing on the purchase of new vehicles in cities, Schmidt (2020) found that the claim that one shared car eliminates roughly three car purchases annually does not apply to high status cars such as SUVs or larger vehicles like vans. Similarly, Li and Kamargianni's (2020) research on how carsharing affects private car ownership and public transport demand established that people who take long trips are less likely to give up their private car in favor of carsharing. As one may reasonably assume that P2P sharing is also a less attractive option in such cases, the debate around carsharing as a means of reducing car traffic remains unresolved.…”
Section: Discussion and Research Agendamentioning
confidence: 99%
“…In cities eagerly visited by tourists, apart from transparent information, what counts is the possibility of quick calculation of travel costs. Reasonable solutions can be reached by trial and error, but it is increasingly common for cities to form relationships or communities and share experiences [14]. The agreements concern shared information networks and such solutions as several-day public transport tickets, which are valid in several cities, and is accompanied by an offer of journeys, e.g., by train between associated towns [9,15].…”
Section: Need For New Ways To Use Available Means Of Transportmentioning
confidence: 99%